2018
DOI: 10.1016/j.jcomm.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Cod stories: Trade dynamics and duration for Norwegian cod exports

Abstract: In recent years, trade dynamics have been receiving increased attention, and the general literature indicates that commodities are different. In this paper, the duration of trade relationships for Norwegian export firms to various markets is investigated for six product forms of one commodity, cod. The results indicate that the duration of most trade relationships is very short, and shorter than what is normally reported in the literature. Still, the substantial variation in duration by product form and factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 64 publications
(63 reference statements)
0
22
0
Order By: Relevance
“…Asche et al [45] found that at least 45% of Norwegian cod exports fail after the first year of trading. Using a Cox model, the authors concluded that distance, GDP, GDP per capita, firm size, and the number of shipments significantly influence the duration of cod exports.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Asche et al [45] found that at least 45% of Norwegian cod exports fail after the first year of trading. Using a Cox model, the authors concluded that distance, GDP, GDP per capita, firm size, and the number of shipments significantly influence the duration of cod exports.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The main reason is the lack of clarification on whether the trade relationship began in 1996 or earlier. The last year of trading, 2019, was taken as the right-censoring, as done in related studies [45,48,49]. Multiple spells were included as a dummy, in line with similar studies [7,36].…”
Section: Empirical Modelmentioning
confidence: 99%
“…al., 2012;Esteve-Pèrez et. al., 2013), a result that also is evident for trade in seafood (Asche et. al., 2018;Straume, 2017).…”
Section: Introductionmentioning
confidence: 66%
“…The study also provides evidence of frozen cod prices leading the fresh cod prices. Asche et al (2018) examine the trade dynamics and duration with respect to six different product forms of cod exports from Norway. They conclude that trade dynamics and the duration of trade relationships vary substantially for different forms of cod exports.…”
Section: A Brief Review Of Fisheries Related Issues and Fisheries Submentioning
confidence: 99%